Tumor Cell-Derived Exosomal miR-770 Inhibits M2 Macrophage Polarization via Targeting MAP3K1 to Inhibit the Invasion of Non-small Cell Lung Cancer Cells - Liu, Jixian; Luo, Ruixing; Wang, Junbin; Luan, Xinyu; Wu, Da; Chen, Hua; Hou, Qinghua; Mao, Guangxian; Li, Xiaoqiang (Frontiers in Cell and Developmental Biology, 2021)
Background: Non-small cell lung carcinoma (NSCLC) is a type lung cancer with high malignant behaviors. MicroRNAs (miRNAs) are known to be involved in progression of NSCLC. In order to explore potential targets for the treatment of NSCLC, bioinformatics tool was used to analyze differential expressed miRNAs between NSCLC and adjacent normal tissues. Methods: bioinformatics tool was used to find potential targets for NSCLC. Cell proliferation was investigated by Ki67 staining. Cell apoptosis was measured by flow cytometry. mRNA and protein expression in NSCLC cells were detected by RT-qPCR and Western-blot, respectively. Transwell assay was performed to test the cell migration and invasion. In order to investigate the function of exosomal miRNA in NSCLC, in vivo model of NSCLC was constructed. Results: MiR-770 was identified to be downregulated in NSCLC, and miR-770 agomir could significantly inhibit NSCLC cell proliferation through inducing the apoptosis. Additionally, the metastasis of NSCLC cells was decreased by miR-770 agomir. MAP3K1 was identified to be the target mRNA of miR-770. Meanwhile, tumor cell-derived exosomal miR-770 inhibited M2 macrophage polarization via downregulation of MAP3K1, which in turn suppressed NSCLC cell invasion. Besides, tumor cell-derived exosomal miR-770 markedly decreased NSCLC tumor growth in vivo through suppressing M2 macrophage polarization. Conclusion: Tumor cell-derived exosomal miR-770 inhibits M2 macrophage polarization to inhibit the invasion of NSCLC cells via targeting MAP3K1. Thus, this study provided a new strategy for the treatment of NSCLC.